(untitled) (Experimental biology, 2015)
Wheat varieties contrasting on tolerance (according to preliminary results ) to cadmium - Kazakhstanskaya -3 , Kazakhstanskaya rannnaya and Shagala were taken for the study of lipid peroxidation and chlorophyll content. With increasing concentration of cadmium increased level of lipid peroxidation and decreased the concentration of chlorophyll a and b. The level of lipid peroxidation was higher in the sensitive to cadmium Shagala variety l compared to tolerant ones. In resistant varieties Kazakhstanskaya-3 and Kazakhstanskaya rannnaya content of photosynthetic pigments nder cadmium stress was higher than that of non-resistant variety Shagala. These biochemical and physiological parameters can be used as markers for the selection of tolerant varieties of plants to adverse environmental conditions.